Glass powder and glass for sealing titanium alloy as well as preparation method and application of glass powder and glass
By developing an alkali-free and silicon-free titanium alloy sealing glass powder, prepared using specific raw materials and processes, the problem of poor sealing performance of existing glass powder at high temperatures is solved, and efficient and low-cost production is achieved process and improve the mechanical and sealing performance of the sealing device.
Patent Information
- Application Number
- CN202411630979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-21
AI Technical Summary
The existing glass powder for sealing titanium alloys contains alkali metals and silicon elements, resulting in poor sealing performance with titanium alloys at high temperatures, and the production process is complicated, which increases production costs.
An alkali-free and silicon-free titanium alloy sealing glass powder was developed, using 18% to 35% SrO, 17% to 35% BaO, 14% to 25% B2O3, 16% to 26% Al2O3, 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 1% to 2% ZrO2 and 5% to 6% CaF2 raw materials were made, and glass powder with excellent properties was prepared by specific melting and grinding processes.
The sealing device prepared by this glass powder has stable mechanical properties and high sealing properties, high production efficiency, low production cost, and does not require nitriding treatment and laser cleaning, which significantly improves production efficiency.
Smart Images

Figure BDA0005135909360000041 
Figure BDA0005135909360000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass sealing, and in particular to glass powder for titanium alloy sealing, glass, and a preparation method and application thereof. Background Art
[0002] Titanium and titanium alloys have many ideal properties, including high strength, low specific gravity, high chemical corrosion resistance and medium high temperature stability, and are known as the "metal of the 21st century". In recent years, glass sealing parts made of this metal, including aviation plugs, sensors, electrode plugs and other types of products, have been widely used in aerospace, underwater detection, oil drilling, chemical industry and other fields, and are expected to replace stainless steel, Kovar alloy glass and other sealing devices, and become a new generation of high-performance glass sealing products.
[0003] Glass powder that is hermetically sealed with titanium and titanium alloys must meet three main criteria in order to form a high sealing performance. First, the coefficient of thermal expansion (CTE) of the glass must match that of titanium from room temperature to the glass transition temperature; second, the glass must wet and bond with titanium at high temperatures without forming gaseous substances at the bonding surface; finally, the high-temperature bonding point of the glass and titanium must be lower than the phase transition temperature of titanium and titanium alloys.
[0004] At present, the sealing glass used to match the expansion coefficient of titanium and titanium alloys is traditional silicate glass with alkali metals. Due to the presence of alkali metals, bubbles are formed at the glass-metal interface after high-temperature melting and sealing, which will reduce the sealing performance of the sealing parts. At the same time, titanium is a highly reactive metal at high temperatures and will form new compounds with silicon dioxide. This compound will deteriorate the adhesion between glass and titanium alloy, thereby causing the mechanical properties and sealing performance of the sealing device to fail to meet the requirements. In view of this, at present, this kind of glass needs to be nitrided before sealing with titanium, and then melt-sealed with this kind of glass at high temperature. After the sealing is completed, the surface of the titanium alloy is laser cleaned to remove the surface nitride, which greatly increases the production cost and reduces the production efficiency.
[0005] Based on the above research, there is a need to provide a glass powder for sealing titanium alloys that does not contain silicon and alkali metal elements. The sealing device prepared by the glass powder can meet the requirements of mechanical properties and sealing performance, and at the same time has high production efficiency and low production cost. Summary of the invention
[0006] Technical issues
[0007] The object of the present invention is to provide an alkali-free, silicon-free glass powder for titanium alloy sealing. The sealing device prepared by the glass powder has stable performance, good mechanical properties and sealing properties, high production efficiency and low production cost.
[0008] Technical Solution
[0009] In a first aspect, the present application provides a glass powder for sealing titanium alloys. The glass powder for sealing titanium alloys is made of the following raw materials in weight percentage: 18% to 35% SrO, 17% to 35% BaO, 14% to 25% B2O3, 16% to 26% Al2O3, 1% to 2% ZrO2 and 5% to 6% flux.
[0010] In some embodiments, the flux is CaF2. CaF2 can make the glass network more tightly connected, reduce the softening and melting temperature of the glass system, and easily form a mixed system of microcrystalline phase and glass phase. The generation of microcrystals can enhance the network structure and improve the strength and environmental resistance of the glass.
[0011] In some embodiments, the expansion coefficient α of the titanium alloy sealing glass powder is 94×10 -7 / ℃~102×10 -7 / ℃.
[0012] In some embodiments, the transition temperature Tg of the titanium alloy sealing glass powder is 544°C to 587°C.
[0013] In some embodiments, the glass powder has a particle size of 5 to 50 μm.
[0014] The second aspect of the present application provides a method for preparing glass powder for titanium alloy sealing, comprising the following specific steps:
[0015] a. Weigh the raw materials of titanium alloy sealing glass powder and mix them to obtain a mixture;
[0016] b. Take 1 / 3 to 2 / 5 of the above mixture and melt it at 1300 to 1400 ° C for 2 to 4 hours to obtain melt 1, and then quench it with water to obtain flux cullet;
[0017] c. melting the above-mentioned fluxing cullet and the remaining mixture at 1300-1400°C for 1-3h to obtain a melt 2, and quenching with water to obtain glass cullets;
[0018] d. Grind the above glass pieces in a ball mill and sieve to obtain glass powder.
[0019] In some embodiments, the raw materials in step a are specifically: 18% to 35% SrO, 17% to 35% BaO, 14% to 25% B2O3, 16% to 26% Al2O3, 1% to 2% ZrO2 and 5% to 6% CaF2.
[0020] In some embodiments, in step d, sieving is performed using a sieve with a mesh size of 250.
[0021] A third aspect of the present application provides a glass, which is made using the glass powder for titanium alloy sealing as described in any one of the above items.
[0022] A fourth aspect of the present application provides the use of glass powder for titanium alloy sealing prepared by any of the preparation methods described above in the preparation of sealing components.
[0023] In some embodiments, the preparation of the seal comprises the following steps:
[0024] 1) The glass powder is granulated and dry pressed to form a glass embryo;
[0025] 2) pre-oxidizing the central column at 400-550° C. for 10-30 min to obtain a pre-oxidized central column;
[0026] 3) The pre-oxidized central column, the glass embryo and the titanium alloy shell sleeved on the outside of the glass embryo are placed in a sealing graphite mold in sequence to form an assembly component, and then the assembly component and the sealing graphite mold are placed in a sealing furnace, and protective gas is introduced, and the temperature is raised to 820-860° C. and kept warm for 15-25 minutes for sealing;
[0027] 4) Cooling to 450-550° C., keeping the temperature for 20-30 min, and then cooling to room temperature to obtain a seal.
[0028] In some embodiments, the titanium alloy shell is made of TC4 titanium alloy; the center column is made of iron-nickel alloy 4J50.
[0029] In some embodiments, the sealing furnace is a tubular furnace; the protective gas is an inert gas, preferably one of argon, helium, neon or krypton; the purity of the protective gas exceeds 99.99%.
[0030] Technical Effects
[0031] When preparing the glass powder of the present invention, a flux block is first prepared, which can effectively ensure the stability of the performance parameters of the molten glass, so that each batch of products produced by the method of the present invention can obtain batch consistency glass. At the same time, the glass powder provided by the present invention has excellent performance, has an expansion coefficient that matches titanium, and the temperature of sealing with the titanium alloy is lower than the phase transition temperature of the titanium alloy 882°C, and the final product is obtained after sealing with the titanium alloy, and no nitriding treatment and laser cleaning are required, which improves production efficiency and reduces production costs. In addition, the glass made from the glass powder provided by the present invention is an alkali-free, silicon-free boroaluminate system glass, which forms a mutually penetrating solid-phase reaction product at the glass-metal interface during the high-temperature melting process of glass and titanium, avoiding the generation of gaseous phase reactants, thereby enhancing the adhesion between glass and metal, and making the glass well combined with titanium and titanium alloys to form a highly sealed seal. Furthermore, the seal prepared from the glass powder provided by the present invention not only has good sealing performance, but also has excellent compressive resistance and insulation properties. DETAILED DESCRIPTION
[0032] To facilitate the technical solution of the application, the following first provides a general description and definition of the terms and expressions involved in the application.
[0033] The terms "comprises", "includes" or any other variation thereof are intended to cover non-exclusive inclusion, such that a process, method, article or apparatus that includes a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article or apparatus. In the absence of further limitations, an element defined by the phrase "comprises a ..." does not exclude the presence of additional identical elements in the process, method, article or apparatus that includes the element.
[0034] First, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The phrase "in a preferred embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it an embodiment that is exclusive or selectively mutually exclusive with other embodiments.
[0035] In each group of comparative experiments provided in this application, unless otherwise specified, except for the differences indicated in each group, other experimental conditions, materials, etc. are kept consistent to ensure comparability.
[0036] The reagents, instruments, equipment and experimental methods used in the embodiments of the present invention, unless otherwise specified, are all commercially available. Experimental methods without specific conditions are conventional methods and conventional conditions well known in the art, or are based on the conditions recommended by the instrument manufacturer.
[0037] The following is a further description of the glass powder for titanium alloy sealing, glass, and preparation method and application thereof provided in the present application.
[0038] Example 1: Preparation of glass powder for titanium alloy sealing
[0039] Weigh the raw materials of glass powder for titanium alloy sealing: 20% SrO, 30% BaO, 19% B2O3, 25% Al2O3, 1% ZrO2, and 5% CaF2, and mix the raw materials to obtain a mixture; take about 1 / 3 to 2 / 5 of the mixture (1 / 3 in this embodiment) and melt it at 1300-1400°C for 2-4 hours to obtain a melt 1, and then quench it with water to obtain a fluxing cullet; melt the fluxing cullet and the remaining mixture at 1300-1400°C for 1-3 hours to obtain a melt 2, and then quench it with water to obtain glass pieces; grind the glass pieces in a horizontal ball mill (model: LG-QS-5), and sieve them with a sieve with a mesh of 250 mesh to obtain glass powder (TIG-1).
[0040] Example 2: Preparation of glass powder for titanium alloy sealing
[0041] The difference from Example 1 is that the raw materials of the matrix glass powder are replaced with: 25% SrO, 25% BaO, 22% B2O3, 20% Al2O3, 2% ZrO2, 6% CaF2. Finally, glass powder (TIG-2) is obtained.
[0042] Example 3: Preparation of glass powder for titanium alloy sealing
[0043] The difference from Example 1 is that the raw materials of the matrix glass powder are replaced with: 35% SrO, 17% BaO, 25% B2O3, 16% Al2O3, 2% ZrO2, 5% CaF2. Finally, glass powder (TIG-3) is obtained.
[0044] Example 4: Preparation of glass powder for titanium alloy sealing
[0045] The difference from Example 1 is that the raw materials of the matrix glass powder are replaced with: 18% SrO, 35% BaO, 14% B2O3, 26% Al2O3, 1% ZrO2, 6% CaF2. Finally, glass powder (TIG-4) is obtained.
[0046] Example 5: Glass powder performance test
[0047] The expansion coefficient α of the glass powder was measured using an expansion coefficient measuring instrument (model: CSI-771); the transformation temperature Tg of the glass powder was measured using a differential scanning calorimeter (model: DSC 5+). The results are shown in Table 1. The glass powder prepared by the present invention has excellent performance and has an expansion coefficient that matches titanium (the expansion coefficient α of the glass powder for titanium alloy sealing is 90×10-7 / ℃~105×10 -7 / ℃), and the sealing temperature with titanium alloy is lower than the phase transition temperature of titanium alloy 882℃.
[0048] Table 1 Performance results of glass powder
[0049]
[0050]
[0051] Example 6: Preparation of seal
[0052] The glass powder obtained in Example 1 was granulated and dry pressed to form a glass embryo. Titanium alloy (TC4 titanium alloy, purchased from Shaanxi Tiancheng Aviation Materials Co., Ltd.) was processed into a Φ35mm, 3mm thick disc, and then two through holes with a diameter of Φ5mm were processed on the disc. A Φ2mm center column (iron-nickel alloy 4J50) was pre-oxidized at 400-550°C (450°C in this example) for 10-20min (15min in this example). Then, the pre-oxidized central column, the glass embryo and the titanium alloy sleeved on the outside of the glass embryo are sequentially placed in a sealing graphite mold to form an assembly component, and then the assembly component and the sealing graphite mold are placed in a tubular atmosphere furnace (model: GSL-1750X-KS), and an inert gas (argon) is introduced as a protective gas, and the gas flow rate is 25L / min. The temperature is raised to 830-860°C (850°C in this embodiment), and the temperature is kept for 15-25min (20min in this embodiment) to perform sealing. Finally, the temperature is lowered to 480-550°C (500°C in this embodiment), and the temperature is kept for 20-30min (25min in this embodiment), and then cooled to room temperature to obtain a sealing member (TIG-1').
[0053] Example 7: Preparation of seal
[0054] The difference from Example 6 is that the "glass powder obtained in Example 1" is replaced by the "glass powder obtained in Example 2". Finally, a sealing member (TIG-2') is obtained.
[0055] Example 8: Preparation of seal
[0056] The difference from Example 6 is that the "glass powder obtained in Example 1" is replaced by the "glass powder obtained in Example 3". Finally, a sealing member (TIG-3') is obtained.
[0057] Example 9: Preparation of seal
[0058] The difference from Example 7 is that the "glass powder obtained in Example 1" is replaced by the "glass powder obtained in Example 4". Finally, a sealing member (TIG-4') is obtained.
[0059] Comparative Example 1: Preparation of seal
[0060] The difference from Example 6 is that the glass powder obtained in Example 1 is replaced with titanium sealing glass powder (purchased from Nippon Electric Glass Co., Ltd., item number ST-4W / K). Finally, a sealing member (TIG-5') is obtained.
[0061] Comparative Example 2: Preparation of seal
[0062] The difference from Example 6 is that the glass powder obtained in Example 1 is replaced with titanium sealing glass powder (purchased from Shenzhen Himax Material Technology Co., Ltd., item number MDM610M). Finally, a sealing member (TIG-6') is obtained.
[0063] Example 10: Sealing performance test
[0064] The performance tests of the seals prepared in Examples 6-9 and Comparative Examples 1-2 were performed as follows:
[0065] (1) Sealing performance test: Use a helium mass spectrometer leak detector (model: ZQJ-230D) to measure the sealing performance of the sealed product. If the airtightness is ≤1.0×10-9Pa·m3 / s, it meets the sealing requirements of the product.
[0066] (2) Insulation resistance test: Use a high resistance meter (model: ZC46) to measure the insulation of the sealed product. If the insulation resistance is greater than 10GΩ / 500VDC, the product meets the insulation requirements.
[0067] (3) Tensile test: The tensile test is carried out on a tensile tester (model: ZP-5000N). If the core column does not fall off after applying a pressure of 1000N on the center column, it meets the sealing strength requirements;
[0068] The results are shown in Table 2. The seals prepared by the present invention exceed the requirements specified in the standards, and the sealing, insulation and pressure resistance in the performance test are far better than those of the comparative examples.
[0069] Table 2 Performance results of seals
[0070]
[0071] The above specific implementation methods further illustrate the purpose, technical solutions and beneficial effects of the present application in detail. It should be understood that the above are only specific implementation methods of the present application and are not used to limit the protection scope of the present application. Any modifications, equivalent substitutions, improvements, etc. made on the basis of the technical solutions of the present application should be included in the protection scope of the present application.
Claims
1. A glass powder for titanium alloy sealing, characterized in that: The titanium alloy sealing glass powder is made of the following raw materials in percentage by weight: 18% to 35% SrO, 17% to 35% BaO, 14% to 25% B2O3, 16% to 26% Al2O3, 1% to 2% ZrO2 and 5% to 6% CaF2; the expansion coefficient α of the titanium alloy sealing glass powder is 94×10 -7 / ℃~102×10 -7 / ℃, transition temperature Tg is 544℃~587℃.
2. The glass powder for titanium alloy sealing according to claim 1, characterized in that: The particle size of the glass powder for titanium alloy sealing is 5 to 50 μm.
3. A method for preparing glass powder for titanium alloy sealing, characterized in that: The specific steps include: a. Weigh the raw materials of titanium alloy sealing glass powder and mix them to obtain a mixture; b. Take 1 / 3 to 2 / 5 of the above mixture and melt it at 1300 to 1400 ° C for 2 to 4 hours to obtain melt 1, and then quench it with water to obtain flux cullet; c. melting the above-mentioned fluxing cullet and the remaining mixture at 1300-1400°C for 1-3h to obtain a melt 2, and quenching with water to obtain glass cullets; d. Grind the above glass pieces in a ball mill and sieve to obtain glass powder.
4. The preparation method according to claim 3, characterized in that: The raw materials described in step a are specifically: 18% to 35% SrO, 17% to 35% BaO, 14% to 25% B2O3, 16% to 26% Al2O3, 1% to 2% ZrO2 and 5% to 6% CaF2.
5. The preparation method according to claim 3, characterized in that: In step d, a sieve with a mesh size of 250 is used for sieving.
6. A glass, characterized in that: The glass is made of the titanium alloy sealing glass powder described in any one of claims 1-2.
7. Use of the titanium alloy sealing glass powder prepared by the preparation method according to any one of claims 3 to 5 in the preparation of sealing parts.
8. The use according to claim 7, characterized in that: The preparation of the sealing member comprises the following steps: 1) The glass powder is granulated and dry pressed to form a glass embryo; 2) pre-oxidizing the central column at 400-550° C. for 10-20 min to obtain a pre-oxidized central column; 3) The pre-oxidized central column, the glass embryo and the titanium alloy shell sleeved on the outside of the glass embryo are placed in a sealing graphite mold in sequence to form an assembly component, and then the assembly component and the sealing graphite mold are placed in a sealing furnace, and protective gas is introduced, and the temperature is raised to 830-860° C. and kept warm for 15-25 minutes for sealing; 4) Cooling to 480-550° C., keeping the temperature for 20-30 min, and then cooling to room temperature to obtain a seal.
9. The use according to claim 8, characterized in that: The titanium alloy shell is made of TC4 titanium alloy; the central column is made of iron-nickel alloy 4J50.
10. The use according to claim 8, characterized in that: The sealing furnace is a tubular atmosphere furnace; the protective gas is one of argon, helium, neon or krypton; the purity of the protective gas exceeds 99.99%.